Zambia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria, and Financing Assurances Review-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report, 2005)
This paper examines Zambia's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and a Request for Waiver and Modification of Performance Criteria (PC). Performance under the PRGF-supported program has been good, although there were delays in some structural measures. All but one of the PCs and all benchmarks under the quantitative program for December 2004 were observed. Two structural PCs were observed, and the third one, for end-February 2005, is now a prior action for the completion of the second review.